2012
DOI: 10.1124/mol.112.079616
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Residues in the Transmembrane (TM) 9 to TM11 Region of the Human Equilibrative Nucleoside Transporter Subtype 1 Play an Important Role in Inhibitor Binding and Translocation Function

Abstract: Inhibitor and substrate interactions with equilibrative nucleoside transporter 1 (ENT1; SLC29A1) are known to be affected by cysteine-modifying reagents. A previous study from our laboratory established Cys222 in transmembrane (TM) 6 as the residue responsible for methyl methanethiosulfonate (a membrane-permeable sulfhydryl modifier)-mediated enhancement of the binding of the ENT1 inhibitor nitrobenzylmercaptopurine riboside (NBMPR) in intact cells. However, the capacity of charged sulfhydryl reagents to inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This supports our homology model of hSLC2A9 (Figs 4A and 5A) which also indicates C181 faces the translocation pore. These findings are comparable with other transporters, like the equilibrative nucleoside transporters (ENTs) and concentrative nucleoside transporter (CNT) proteins232425. For instance, a single cysteine, C140, was located within the substrate translocation channel in rat ENT2, where it reacted with pCMBS23.…”
Section: Discussionsupporting
confidence: 79%
“…This supports our homology model of hSLC2A9 (Figs 4A and 5A) which also indicates C181 faces the translocation pore. These findings are comparable with other transporters, like the equilibrative nucleoside transporters (ENTs) and concentrative nucleoside transporter (CNT) proteins232425. For instance, a single cysteine, C140, was located within the substrate translocation channel in rat ENT2, where it reacted with pCMBS23.…”
Section: Discussionsupporting
confidence: 79%
“…There is a large extracellular loop between TM domains 1 and 2 of ENT1, which contains N-linked glycosylation sites (Vickers et al, 1999). TM domains 2, 4, 5 and 9-11 are reported to be critical for nucleoside transport (Endres and Unadkat 2005;SenGupta et al, 2002;Park and Hammond, 2012) and there is a large intracellular loop between TM domains 6 and 7, which serves as a regulatory hub for the transporter (details in following sections). An important feature of ENT1 is sensitivity to inhibition by the nucleoside analog, NBTI (S-(4-Nitrobenzyl)-6-thioinosine).…”
Section: Structure and Functionmentioning
confidence: 99%
“…There are numerous literature reports of using radiolabeled substrates to define the kinetic parameters for natural and modified nucleosides (41)(42)(43)(44)(45)(46)(47)(48). One insightful report is from the Cass laboratory that has extensively studied the mechanism of nucleoside transport using different model systems (41).…”
Section: Conventional Approaches To Study Nucleosidementioning
confidence: 99%
“…Collectively, the application of radiolabeled substrates to measure the kinetics of nucleoside uptake has provided useful information into the mechanism and regulation of nucleoside homeostasis. In addition, this methodology has been applied in studies using sitedirected mutants of various nucleoside transporters to generate structure-activity relationships (SAR) that define structural features required for efficient nucleoside transport (43)(44)(45). These kinetic studies have also found utility in other research areas.…”
Section: Conventional Approaches To Study Nucleosidementioning
confidence: 99%